2020
DOI: 10.1074/mcp.ra119.001504
|View full text |Cite
|
Sign up to set email alerts
|

Phosphotyrosine-based Phosphoproteomics for Target Identification and Drug Response Prediction in AML Cell Lines

Abstract: Acute myeloid leukemia (AML) is a clonal disorder arising from hematopoietic myeloid progenitors. Aberrantly activated tyrosine kinases (TK) are involved in leukemogenesis and are associated with poor treatment outcome. Kinase inhibitor (KI) treatment has shown promise in improving patient outcome in AML. However, inhibitor selection for patients is suboptimal.In a preclinical effort to address KI selection, we analyzed a panel of 16 AML cell lines using phosphotyrosine (pY) enrichment-based, label-free phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 76 publications
1
43
0
Order By: Relevance
“…These results might be the result of the high penetrance of the driving KRAS mutation in these tumors [39] and lack of other activating mutations of oncogenes. Previous studies of our lab in different cancer types showed more heterogeneity in kinase ranking, affiliated by driver mutations [14,40,41]. Previously, Kim et al [42] evaluated three primary cell lines from different metastatic origins of one patient and found clonal heterogeneity in PDAC, with a distinct (phospho)proteomic profiles of each metastatic site.…”
Section: Discussionmentioning
confidence: 80%
“…These results might be the result of the high penetrance of the driving KRAS mutation in these tumors [39] and lack of other activating mutations of oncogenes. Previous studies of our lab in different cancer types showed more heterogeneity in kinase ranking, affiliated by driver mutations [14,40,41]. Previously, Kim et al [42] evaluated three primary cell lines from different metastatic origins of one patient and found clonal heterogeneity in PDAC, with a distinct (phospho)proteomic profiles of each metastatic site.…”
Section: Discussionmentioning
confidence: 80%
“…Projects such as the Cancer Target Discovery and Development and Genomics of Drug Sensitivity in Cancer have evaluated ML as a means to predict drug responses by associating genomic features, gene expression patterns and copy number alterations to drug sensitivity [17][18][19][20][21] . However, this approach has not been systematically applied using large scale proteomics and phosphoproteomics data, even though anecdotal evidence suggests that proteomic-derived features may be able to predict drug responses more accurately that genomic alternatives [22][23][24][25][26] . A limitation has been the low sample throughput of proteomics and phosphoproteomics by liquid chromatography coupled to tandem mass spectrometry (LC-MS/ MS) compared to other omics techniques.…”
mentioning
confidence: 99%
“…The anti-FLT3 cytoplasmic domain antibody also stained the perinuclear region in these ITD-positive cells (Supplementary Figure S1), supporting the results of FLT3-ITD mislocalization. Since these three cell lines have different ITD sequences (Quentmeier et al, 2003;Furukawa et al, 2007;van Alphen et al, 2020), the accumulation of FLT3 in the perinuclear region was independent of inserted amino acid sequences but dependent on an ITD insertion. These results suggest that ITD causes FLT3 retention in the perinuclear compartment in AML cells.…”
Section: Resultsmentioning
confidence: 99%
“…To examine the localization of endogenous FLT3, we performed confocal immunofluorescence microscopic analyses on human leukemia cell lines with an anti-FLT3 luminal-faced N-terminal region antibody. For immunostaining, we chemically fixed and permeabilized THP-1 (acute monocytic leukemia, FLT3 WT/WT ), RS4-11 (AML, FLT3 WT/WT ), MV4-11 (AML, FLT3 ITD/ITD ), MOLM-14 (AML, FLT3 WT/ITD ), and Kasumi-6 (AML, FLT3 ITD/ITD ) (Quentmeier et al, 2003;Furukawa et al, 2007;Wang et al, 2018;van Alphen et al, 2020; Figure 1A). In FLT3-wt leukemia cell lines (THP-1 and RS4-11), the wild-type receptor was mainly found at the PM ( Figure 1B, upper panels).…”
Section: Resultsmentioning
confidence: 99%